Microcatheter contrast injection in stent retriever neurothrombectomy is safe and useful: insights from SWIFT PRIME. (10th November 2017) - Raychev, Radoslav; Jahan, Reza; Saver, Jeffrey L; Nogueira, Raul G; Goyal, Mayank; Pereira, Vitor M; Levy, Elad; Yavagal, Dileep R; Cognard, Christophe; Liebeskind, David
Abstract : Microcatheter contrast injection (MCI) prior to stent retriever deployment for the treatment of acute ischemic stroke may be useful for evaluation of distal anatomy and flow patterns beyond the occlusion. However, prior data from intra-arterialthrombolysis suggested that MCI increases the risk of intracranial hemorrhage (ICH). The safety and utility of MCI has not been investigated in the setting of thrombectomy. Methods: We analyzed the Solitaire With the Intention For Thrombectomy as Primary Endovascular Treatment (SWIFT PRIME) trial to correlate pre-intervention MCI flow with collateral flow, and to investigate its impact on ICH and clinical outcome after thrombectomy with the Solitaire device. Results: MCI was noted in 52% (n=51) of patients with a prevalence for the M2 location of 71% (n=36). Dichotomized correlation demonstrated a strong inverse relationship for partial collaterals with good MCI flow (p=0.004; OR 8.25). None of the MCI variables (presence, number, or grades) correlated with ICH and clinical outcome. The most significant predictors of non-disabled outcome were higher Alberta Stroke Program early CT Score (ASPECTS) (OR 1.61; p=0.0361) and younger age (OR 0.922; p = 0.0109). Higher ASPECTS was also a strong predictor of lower ICH risk (OR 0.501, p=0.0078). Conclusions: Collateral flow inversely correlated with MCI flow in the endovascular arm of the SWIFT PRIME trial. This finding warrants further validation in larger cohorts as MCI may be influenced by individual operator's technique and choice of syringe size. Evaluation of flow and distal anatomy with MCI prior to stent retriever deployment is safe with no evidence of an impact on ICH or clinical outcome. Clinical trial registration: NCT01657461: Post- results